PENGGUNAAN HERBISIDA TRIKLOPIR UNTUK MENGENDALIKAN GULMA PADA PERKEBUNAN KELAPA SAWIT FASE BELUM MENGHASILKAN DAN PENGARUHNYA TERHADAP KEANEKARAGAMAN SERANGGA: Use Of Triclopyr Herbicide To Control Weeds In The Int-Producing Phase Of Palm Oil And Its Effect On Insect Diversity - Efendi, Siska; Akbar, Ilham; Ardi, Ardi (AgriPeat, 2023)
Weed is one of the major problems in immature oil palm plantations. Weed control is carried out to optimize the growth of oil palm plants, and the method commonly used in the field is chemical control with herbicides. The active ingredient of the herbicide used in the field is triclopyr, however herbicide application is thought to affect the diversity of insects, especially those found in lower vegetation, at the same time it is necessary to observe the effect of herbicide application on insect diversity. This study aims to obtain an effective dose of herbicide to control weeds in immature oil palm plants and to determine the effect of herbicide application on insect diversity. This study used a Randomized Block Design (RBD) which consisted of 6 treatments and 4 replications. Triclopyr herbicide treatment doses were 864 g.ha-1, 768 g/ha, 672 g.ha-1, 576 g.ha-1, mechanical weeding and control. Insect sampling method uses insect nets and pitfall traps. The data obtained were analyzed using variance or F test at 5% level and further test was carried out by DMRT at 5% level. The results showed that the best dose of herbicide triclopir was 768 g/ha because it was effective in controlling the weeds of Borreria latifolia, Calopogonium mucunoides and Asystasia gangetica. Triclopyr herbicide application affects the diversity of insects and the even distribution of insects.